The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014 IEEE Virtual Reality (VR) 2014
DOI: 10.1109/vr.2014.6802051
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of an AR-based context-aware assembly support system in object assembly

Abstract: This study evaluates the effectiveness of an AR-based contextaware assembly support system with AR visualization modes proposed in object assembly. Although many AR-based assembly support systems have been proposed, few keep track of the assembly status in real-time and automatically recognize error and completion states at each step. Naturally, the effectiveness of such contextaware systems remains unexplored. Our test-bed system displays guidance information and error detection information corresponding to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 16 publications
1
32
2
Order By: Relevance
“…Khuong et al [13] apply two AR visualization methods for supporting assembly tasks using real-time detection of the assembly status. They found that displaying guidance information as an overlay to the physical target leads to longer completion times than displaying information in a side-by-side manner adjacent to it.…”
Section: Applicability Of Ar Glasses For the Application Domainmentioning
confidence: 99%
“…Khuong et al [13] apply two AR visualization methods for supporting assembly tasks using real-time detection of the assembly status. They found that displaying guidance information as an overlay to the physical target leads to longer completion times than displaying information in a side-by-side manner adjacent to it.…”
Section: Applicability Of Ar Glasses For the Application Domainmentioning
confidence: 99%
“…In past experiments these performed worse than projectionbased approaches [5], but there was already some evidence that approaches on modern AR glasses may perform similarly well with the advantage of not being bound to a specific workspace [4]. Previous comparisons also indicated that side-by-side instructions outperform in-situ instructions using AR glasses [14]. However, we anticipate that these results do no longer hold in light of modern hardware.…”
mentioning
confidence: 86%
“…Stanimirovic et al [25] use a tablet computer for showing in-situ visualizations in form of superimposed 3D animations and additional billboarded textual descriptions. Also in a LEGO DUPLO assembly scenario, Khuong et al [14] proposed a side-by-side visualization for instructing workers. Compared to a wireframe-based in-situ instruction, their results show that spatial separation of the real and the virtual model performed better than the target-aligned in-situ variant.…”
Section: Assembly Tasksmentioning
confidence: 99%
See 2 more Smart Citations